2019
DOI: 10.3389/fneur.2019.01037
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Pattern Classification of Primary Insomnia Using Three Types of Functional Connectivity Features

Abstract: Objective: To explore whether or not functional connectivity (FC) could be used as a potential biomarker for classification of primary insomnia (PI) at the individual level by using multivariate pattern analysis (MVPA).Methods: Thirty-eight drug-naive patients with PI, and 44 healthy controls (HC) underwent resting-state functional MR imaging. Voxel-wise functional connectivity strength (FCS), large-scale functional connectivity (large-scale FC) and regional homogeneity (ReHo) were calculated for each particip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
0
19
1
Order By: Relevance
“…Brain magnetic resonance imaging (MRI) MRI is a non-invasive imaging method to detect features of brain tissue [32]. In particular, MRI is a well-suited technique to visualize and analyse the anatomical properties and abnormalities in the brain.…”
Section: National Institutes Of Health Stroke Scalementioning
confidence: 99%
“…Brain magnetic resonance imaging (MRI) MRI is a non-invasive imaging method to detect features of brain tissue [32]. In particular, MRI is a well-suited technique to visualize and analyse the anatomical properties and abnormalities in the brain.…”
Section: National Institutes Of Health Stroke Scalementioning
confidence: 99%
“…Some of the differences between our results and the other studies were in part due to focusing on different structures, since we only targeted the thalamus, prefrontal cortex, parietal lobe, brain stem, vermis and cerebellar hemispheres, sensorimotor region, auditory cortex, amygdala, and caudate nucleus. These regions have been observed to be affected in patients with insomnia, in addition to several other structures such as the insula or middle frontal gyrus [26,28,45].…”
Section: Sleep Disordersmentioning
confidence: 99%
“…After six weeks of multimodal nonpharmacological therapy, activation was partially restored in the medial prefrontal cortex during the category fluency task, and in the inferior frontal gyrus during the letter fluency task. Other fMRI studies comparing functional connectivity in insomnia patients to that in controls revealed an association with the insular cortex, middle frontal gyrus, prefrontal cortex, parietal lobe (particularly the precuneus), and head of the caudate nucleus [26,27]. Additionally, functional connectivity between the cerebellum and various cortical structures is altered in patients with insomnia [28].…”
Section: Introductionmentioning
confidence: 98%
“…Anxiety is highly interconnected with insomnia because sleep deprivation lowers the psychological threshold for stress tolerance [41,42]. In this work, we assessed the anxiety of Sprague-Dawley rats in an open field test and found that MSZRD significantly reduced behavioral signs of anxiety relative to untreated model animals.…”
mentioning
confidence: 91%